2021
DOI: 10.3390/jmmp5010018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of the Impact of the Electromagnetic Properties of the Die Materials in Electromagnetic Forming of Thin Sheet Metal

Abstract: In electromagnetic forming of thin sheet metal, the die is located within the effective range of the electromagnetic wave. Correspondingly, a current is induced not only in the sheet metal, but also in the die. Like the current in the workpiece, also the current in the die interacts with the electromagnetic wave, resulting in Lorentz forces and changes of the electromagnetic field. With the aim to study the influence of different electromagnetic die properties in terms of specific electric resistance and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The research presented in [ 19 , 20 ] presents the bending of sheet metal specimens in a magnetic field. The results show that the differences in magnetic pulse bending are minimal in comparison to the method described there.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research presented in [ 19 , 20 ] presents the bending of sheet metal specimens in a magnetic field. The results show that the differences in magnetic pulse bending are minimal in comparison to the method described there.…”
Section: Resultsmentioning
confidence: 99%
“…In the presented analysis in manufacturing companies, we came across this phenomenon, i.e., a lack of funds. This presented solution would certainly not burden the companies’ budget considerably, as it would practically only replace the active parts of the forming equipment, which would speed up this work, make it more attractive, and would make it relatively easy for any just-trained worker and increase safety at work [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 Researchers have done a large amount of work on the numerical simulation of EMF process. 7 , 8 , 9 So far, there are still two key problems worthy of special attention: one is the coupling strategy of the electromagnetic field and mechanical field 10 and another is the computational efficiency of complex EMF scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding eddy current in the die, Beckschwarte et al showed how electromagnetic properties of dies can be used to affect the electromagnetic forming process by effecting field and current densities, force vectors and material forming behavior [18]. Therefore, based on the property gradient of the embossing dies by the coating, the interaction of coating and substrate material must be considered regarding the conditions of the embossing process of thin sheet metals.…”
Section: Introductionmentioning
confidence: 99%